2013
DOI: 10.1248/bpb.b12-00460
|View full text |Cite
|
Sign up to set email alerts
|

Cetylpyridinium Chloride Inhibits Receptor Activator of Nuclear Factor-κB Ligand-Induced Osteoclast Formation

Abstract: Osteoclasts are responsible for bone erosion in diseases as diverse as osteoporosis, periodontitis, and rheumatoid arthritis. Antiseptic products have received recent attention as potential therapeutic and preventive drugs in human disease. The purpose of this study was to investigate the effect of the antiseptic cetylpyridinium chloride (CPC) on osteoclast formation using mouse bone marrow-derived macrophages (BMMs). CPC inhibited receptor activator of nuclear factor (NF)-κB ligand (RANKL)-induced osteoclast … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 20 publications
(23 reference statements)
0
4
0
Order By: Relevance
“…23 Also, it has been reported that CPC inhibited osteoclast differentiation in a dose-response way. 32 All these adverse effects of CPC must be considered in clinical applications to treat chronical diseases.…”
Section: Discussionmentioning
confidence: 99%
“…23 Also, it has been reported that CPC inhibited osteoclast differentiation in a dose-response way. 32 All these adverse effects of CPC must be considered in clinical applications to treat chronical diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Blimp1 is a master protein regulating the transcriptional network that improves B cell terminal differentiation. Bcl6 functions opposite to Blimp1 in regulating differentiation of B lymphocytes, and it can inhibit and block terminal differentiation of B lymphocytes (20)(21)(22)(23). High expression of Bcl6 in B cell lymphoma tissues has been associated with poor differentiation grade (24,25).…”
Section: Influence Onblimp1 and Bcl6 Expression May Be Involved In MDmentioning
confidence: 99%
“…CPC helps to fight plaque (Sreenivasan et al ., 2013), gingivitis (Teng et al ., 2016), halitosis (Yaegaki and Sanada, 1992), and bacterial infections (Schaeffer et al ., 2011; Latimer et al ., 2015). Due to these oral care properties, including potential effects on bone signaling (Zheng et al ., 2013), the addition of CPC to dental restorations is also being explored (Tomino et al ., 2016; Yamamoto et al ., 2022). CPC is used in numerous other cosmetics (hair coloring and styling products, deodorant, hair conditioners, and cosmetic biocides) and in the active pharmaceutical industry as an intermediate (PubChem).…”
Section: Introductionmentioning
confidence: 99%